Perjalanan Perempuan Indonesia dalam âMengejarâ Kuota Kursi Parlemen - Agustina, Titien (Muadalah, 2014)
The affirmative action policy through the provision of a 30 % quota of parliamentary seats has been passed three times in legislative electionsâ2004, 2009, and 2014. Yet, the desired representation still cannot be achieved and even the figure of 20% has not been able to accomplish. Whereas, women representation in the parliamentary is something that very basic in order to meet womenâs political rights in the state. Men and women should have the equal opportunity to participate and to have control in running the government. However, there are still few women who plunge into politics. In addition to the dominant role of the party elite and inadequate recruitment system of the legislative candidates, political education is also still very minimal and a strong kinship system have made politics to be the last choice for women. Thus, womenâs lack of interest and desire to get involved in politics results in lack of womenâs representation quota in parliament.